A provisional and evolving framework for standardizing cartilage organoid construction: toward consistency, reproducibility, and clinical translation - Hefei Zhang; Shengdong Yang; Li Junyou; Xinjie Wu; Wei Sun; Rongjie Feng; Fuqiang Gao; Qingyu Zhang (Biofabrication, 2026)
Abstract Cartilage organoids (COs) have emerged as a promising three-dimensional platform for modeling cartilage development, degeneration, and repair, yet their broader application remains constrained by substantial variability in cell sources, construction strategies, culture conditions, and evaluation criteria. This manuscript addresses the critical need for standardization in cartilage organoid research and aims to establish a structured framework for their classification, construction, application, and quality assessment. We systematically summarize the defining features of COs and distinguish them from related cartilage models, then review major cell sources, including embryonic stem cells, induced pluripotent stem cells, mesenchymal stem cells, and periosteum-derived cells, together with scaffold-free and scaffold-assisted fabrication strategies, stepwise induction protocols, bioprinting approaches, bioreactor systems, and key microenvironmental regulators such as hypoxia, mechanical stimulation, and multicellular interactions. Based on this, we propose a literature-informed conceptual framework termed COSS (Cartilage Organoid Standardization System). COSS comprises a three-tier standardization framework encompassing input control, process standardization, and output evaluation. It further defines minimum reporting items and a tiered evaluation framework for disease modeling, drug screening, and regenerative repair, with the aim of harmonizing terminology, reporting requirements, quality attributes, and priorities for future validation. This framework cannot yet be regarded as an experimentally validated production standard or a regulatory-endorsed system. Further work is required to refine the framework and establish reliable quantitative thresholds and specific numerical criteria. Collectively, this work provides an application-oriented roadmap for improving reproducibility, comparability, and translational relevance in cartilage organoid studies. These recommendations could serve as an initial framework for multicenter benchmarking and for supporting future determination of reproducibility for mechanistic studies, preclinical evaluation, or repair-oriented applications.